Risk Factors of Carpal Tunnel Syndrome among Stone-Carving Workers in Chon Buri Province - Intawong, Chanthip; Chantawong, Chantana; Srisuriyawet, Rungrat (Journal of Health Science of Thailand, 2018)
The purposes of this cross-sectional study were to describe the prevalence rate and to examine association between personal, working condition factors and Carpal Tunnel Syndrome (CTS) among stone-carving workers. The participants consisted of 183 stone-carving workers who were working in industry or at home. Data were collected from August, 2007 to January, 2008. Data gathering methods were interview, measurements of wrist dimensions, diameters of carving tools handles and electro diagnostic test. Data were analyzed by descriptive statistics, chi-square test and odds ratio (OR). Results revealed that the overall prevalence rate of CTS for 156 workers participating to the end of the study was 29.5 percent: 15.7 percent in male, 38.7 percent in female, 27.6 percent of left hand and 23.7 percent of right hand. Four personal factors were significantly associated with CTS: sex (OR 3.50, 95%CI 1.70, 7.20), BMI (OR 3.93, 95%CI 1.62, 9.54), wrist dimension of left hand (OR 3.00, 95%CI 1.64, 7.75), and coffee drinking (OR 2.46, 95%CI 1.13, 5.35). For working condition factor, rest duration (OR 2.77, 95%CI 1.34, 5.71) was a significantly associated with CTS. Also, house chores (OR 2.12, 95%CI 1.02, 4.41) was a significant factor. This study suggested that screening and monitoring of personal and working conditions were crucial to reduce prevalence rate of CTS through a health promotion program at worksite.